Mergers and Acquisitions in Islamic Banking In Indonesia: A Study on BSI and Bank Victoria Syariah - Ahmad, Habibi Zaman Riawan (UIN Salatiga, 2023)
Mergers and acquisitions (MA) in Islamic banking in Indonesia can be viewed from the strategic interests of each bank. This research aims to examine the patterns of MA in Bank Syariah Indonesia (BSI) and Bank Victoria Syariah in Indonesia. It also discusses the positive and negative implications of the MA of these two banks, as seen in the developments before and after the MA. This research employs BOCR (Benefit, Opportunity, Cost, and Risk) analysis to assess the extent to which MA patterns occur in the merger outcomes at BSI. It also utilizes CAMEL (Capital Asset Earnings and Liquidity) analysis to evaluate the post-acquisition banking health at Bank Victoria Syariah. The research descriptively explains the MA conditions in these two Islamic banks in Indonesia and the impact of MA on the banks, employees, customers, and the general public. The study results indicate that themerger of three state-owned Islamic banking companies, namely Bank Syariah Mandiri, BRI Syariah, and BNI Syariah, into BSI was carried out not only to expand the market share of Islamic banking but also due to cost considerations. At the same time, the acquisition of Bank Victoria Syariah was made due to capital needs as required by the regulator.